THE ASSOCIATION OF RHEUMATOLOGISTS OF RUSSIA: FROM THE PAST TO THE PRESENT AND THE FUTURE - E. L. Nasonov; V. N. Amirdzhanova; R. M. Balabanova; L. I. Alekseeva; L. N. Denisov (Научно-практическая ревматология)
The All-Russian public organization «The Association of Rheumatologists of Russia» (ARR) is in the forefront of the history and present-day activity of Russian rheumatology. In 1928, the Committee on Rheumatism and Control was set up, which was essentially the predecessor to All-USSR (1964) and All-Russian (1987) research societies of rheumatologists, which were succeeded by ARR (1991). Today ARR is one of the largest and influential public health organizations in Russia, the activity of which has been able to sustain and strengthen a rheumatology service in the country and to train a highly experienced professional community rendering care for patients with rheumatic diseases. Innovative biological agents that could substantially improve treatment results have been recently designed. However, cardinal prognosis improvement is associated not only with the introduction of the innovative medicines, but also with the improvement of early-iagnosis-based pharmacotherapy strategy that determines the possible initiation of very early (a window of opportunity) active tightly controlled anti-inflammatory therapy whose goal is to maximally achieve active remission (to treat to target). ARR jointlywith European rheumatologists has been engaged in this international initiative shortly since its creation in 2010. Further training of rheumatologists has been one of the main tasks of ARR at all times. ARR has proposed a learningthrough-life model of continuing medical education, by involving rheumatologists at full-term and on-line advanced training cycles, seminars, schools, conferences, meetings, and congresses. At the website of the V.A. Nasonova Research Institute of Rheumatology there is a portal of education programs in rheumatology, which is available to all rheumatologists of the country. Today ARR unites not only rheumatologists, but also physicians of related professions: cardiologists, gastroenterologists, aftercare specialists, traumatologists/orthopedists, endocrinologists, neurologists, and psychiatrists. In the past decade, the All-Russian society of disabled people «Nadezhda (Hope) Association» has joined ARR in implementing its measures.